Effect of graphene content on the electrochemical and dielectric properties of metallopolymer-based composites - Aydin, Derya; Biryan, Fatih (Elsevier, 2026)
In this study, ferrocene-functionalized tyrosine-based homopolymer poly(Tyr-Fc)/nanographene composites 3 wt %, 5 wt%, and 10 wt% were prepared and systematically investigated in terms of their structural, thermal, dielectric and electrochemical properties. The structural characterizations by FT-IR, SEM, and XRD confirmed the successful incorporation of nanographene into the polymer matrix, resulting in improved crystallinity and surface morphology. Thermal analysis revealed enhanced thermal stability in the composites, with the decomposition temperature and residual weight significantly increasing with graphene loading. Dielectric measurements demonstrated that the dielectric constant and AC conductivity increased dramatically with higher nanographene content, reaching 84.34 and 1.25 x 10-4 S/cm at 10 wt%, respectively. However, this improvement was accompanied by a sharp rise in dielectric loss, suggesting a trade-off between enhanced conductivity and energy dissipation. Electrochemical characterization via cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) revealed that the redox processes were diffusion-controlled and that increasing graphene content improved electron transfer kinetics and charge transport efficiency. The composite with 10 wt % graphene exhibited the highest current response and lowest charge transfer resistance. Overall, the synergistic interaction between ferrocene and graphene enhances the multifunctional performance of the composites, making them promising candidates for applications in electrochemical sensors, energy storage devices, and optoelectronic components.
Keywords: Graphene composites; Ferrocene-functional polymer; Electrochemical performance; Dielectric properties; Nanomaterials; Hybrid materials